The role of the chronic care model in promoting the management of the patient with rare liver disease - Pericleous, M; Kelly, C; Ala, A; De Lusignan, S (Taylor and Francis, 2018)
Introduction: The chronic care model (CCM) provides a holistic approach for managing chronic illnesses. Patients with rare liver diseases (RLD) have complex needs, impaired quality of life and often life-threatening complications. Most RLD meet the criteria for a long-term chronic condition and should be viewed through the prism of CCM. We aimed to ascertain whether the CCM has been considered for the frequently-encountered RLD.